Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1080/03004430.2013.818989
|View full text |Cite
|
Sign up to set email alerts
|

Primary physical education perspective on creativity: the nature of creativity and creativity fostering classroom environment

Abstract: From the beginning of the twenty-first century, many authorities and educational policies had begun to campaign their curricula towards the promotion of creativity. Researchers' interest turned to teachers' perceptions, implicit theories and beliefs about creativity-related issues which reflect and influence their behaviours and actions in classroom settings. Till today, no research recorded physical educators' (PEds) perceptions about creativity-(PAC) related issues, although many EU member states promote cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 21 publications
0
18
1
3
Order By: Relevance
“…It is generally accepted that creativity is a significant result of schooling . Since the beginning of the 21st century may countries have begun to adopt educational policies designed to promote creativity . Torrance defined creativity as the process of becoming sensitive to problems, deficiencies, gaps in knowledge, missing elements, disharmonies and so on; identifying the difficulty; searching for solutions, making guesses, or formulating hypotheses about the deficiencies; retesting and testing hypotheses and possibly modifying these and retesting them and, finally, communicating the results.…”
mentioning
confidence: 99%
“…It is generally accepted that creativity is a significant result of schooling . Since the beginning of the 21st century may countries have begun to adopt educational policies designed to promote creativity . Torrance defined creativity as the process of becoming sensitive to problems, deficiencies, gaps in knowledge, missing elements, disharmonies and so on; identifying the difficulty; searching for solutions, making guesses, or formulating hypotheses about the deficiencies; retesting and testing hypotheses and possibly modifying these and retesting them and, finally, communicating the results.…”
mentioning
confidence: 99%
“…Many researchers explored teachers' implicit theories about creativity-related issues (Johnson, Runco, & Raina, 2003;Runco, 1984;Runco, Johnson, & Baer, 1993), as well as other synonymous terms such as perceptions, beliefs, views, stances and conceptions (Bolden, Harries, & Newton, 2010;Chien & Hui, 2010;Craft, Cremin, Burnard, & Chappell, 2007;Diakidoy & Kanari, 1999;Fleith, 2000;Fryer & Collings, 1991;Gregoriadis, Zachopoulou, & Konstantinidou, 2011;Kampylis, Bekri, & Saariluoma, 2009;Kokotsaki, 2011;Konstantinidou, Gregoriadis, & Grammatikopoulos, 2011;Konstantinidou, Gregoriadis, Grammatikopoulos, & Michalopoulou, 2013;Konstantinidou, Michalopoulou, Aggelousis, & Kourtesis, 2011Martin, Craft, & Tillema, 2002;Park, Lee, Oliver, and Cramond, 2006;Tan 1999Tan , 2001Tin, Manara, & Ragawanti, 2010). A systematic analysis and synthesis of the existing literature on K-12 teachers' implicit theories, beliefs or conceptions about creativity (Andiliou & Murphy, 2010) revealed that the majority of the studies explored one of the three aspects: (a) creativity as a construct, (b) the profile of creative individuals and (c) the creativity supportive classroom environment.…”
Section: Introductionmentioning
confidence: 98%
“…Few attempts have been made to explore the PE perspective on creativity through the lenses of physical educators (PEds) regarding the nature of creativity, the characteristics of the creative students, their creative outcomes and the creativity-fostering classroom environment (Konstantinidou, Gregoriadis, & Grammatikopoulos, 2011;Konstantinidou, Gregoriadis et al, 2013;Konstantinidou, Michalopoulou et al, 2011. These attempts have been made on the level of primary PE.…”
Section: Introductionmentioning
confidence: 99%
“…Related to the explanation, then one of the efforts to bridge the development of student creativity is through learning physical education in the school environment (Cheung, 2010). But unfortunately, research on creativity is still rarely done in the world of education, especially physical education (Konstantinidou, Michalopoulou, Agelousis, & Kourtesis, 2013). There is a learning model that is expected to be able to increase the creativity that is owned by students is by applying problem based learning model.…”
Section: Introductionmentioning
confidence: 99%